Статистические методы контроля качества процессов - Гуменная, Т. С. (ХНУРЭ, 2009)
There are considered the statistical methods of monitoring of processes quality in the report. The theory of Karou Ishikawa tells that the quality is not only quality of a product, but also after saling service, quality of management, the company itself and a human life.
Keywords: контроль качества процессов; статистические методы контроля